Association Between Caries Experience and School Performance in an Island Community: Full-Time versus Part-Time Public Schools - Monica Gentil Mattos; Paula Perrota Santos; Ivete Pomarico Ribeiro de Souza; Ronir Raggio Luiz; Lucianne Cople Maia; Aline de Almeida Neves (Association of Support to Oral Health Research (APESB), 2022)
Objective: To investigate the association between caries experience and school performance among children and adolescents living in an island community without fluoridated water supply and to compare data according to the type of attended school (full-time or part-time). Material and Methods: A cross-sectional oral health survey in a convenience sample of students (n=147) attending four public schools was performed. Students were examined by one calibrated dentist in the school environment to the obtain prevalence of dental caries (DMFT/dmft) and its consequences using the PUFA/pufa index. Self-reported oral health behavior was also accessed. Data from each student's school performance and absenteeism were extracted from official sources and the school performance was classified into "good" and "fair". The final sample consisted of 120 students. Descriptive statistics, Mann-Whitney, Kruskal-Wallis, chi-square tests and binary logistic regression were performed to evaluate collected data. Results: Students´ age ranged between 5 to 19 years (10±4.3). DMFT/dmft mean were 1.3 (±2.3) and 3.05 (±3.4), respectively. Conclusion:Participants from the full-time school presented better oral health status than their peers in the part-time schools (p<0.05). A significant association was found between the prevalence of caries-free participants and good school performance when the factor age range was controlled (OR=2.87). Moreover, attendance to full-time schools appeared to be a protective factor for good oral health conditions.